Neural basis for behavioral plasticity during the parental life-stage transition in mice - Miyamichi, Kazunari (Frontiers in Neural Circuits, 2024)
Parental care plays a crucial role in the physical and mental well-being of mammalian offspring. Although sexually naïve male mice, as well as certain strains of female mice, display aggression toward pups, they exhibit heightened parental caregiving behaviors as they approach the time of anticipating their offspring. In this Mini Review, I provide a concise overview of the current understanding of distinct limbic neural types and their circuits governing both aggressive and caregiving behaviors toward infant mice. Subsequently, I delve into recent advancements in the understanding of the molecular, cellular, and neural circuit mechanisms that regulate behavioral plasticity during the transition to parenthood, with a specific focus on the sex steroid hormone estrogen and neural hormone oxytocin. Additionally, I explore potential sex-related differences and highlight some critical unanswered questions that warrant further investigation.